Catalog of Differentially Expressed Long Non-Coding RNA following Activation of Human and Mouse Innate Immune Response - Roux, Benoit T.; Heward, James A.; Donnelly, Louise E.; Jones, Simon W.; Lindsay, Mark A. (Frontiers in Immunology, 2017)
Despite increasing evidence to indicate that long non-coding RNAs (lncRNAs) are novel regulators of immunity, there has been no systematic attempt to identify and characterise the lncRNAs whose expression are changed following the induction of the innate immune response. To address this issue, we have employed next generation sequencing data to determine the changes in the lncRNA profile in 4 human (monocytes, macrophages, epithelium and chondrocytes) and 4 mouse cells types (RAW 264.7 macrophages, bone marrow derived macrophages, peritoneal macrophages and splenic dendritic cells) following exposure to the pro-inflammatory mediators, lipopolysaccharide (LPS) or interleukin-1. We show differential expression of 204 human and 210 mouse lncRNAs, with positional analysis demonstrating correlation with immune related genes. These lncRNAs are predominantly cell-type specific, composed of large regions of repeat sequences and show poor evolutionary conservation. Comparison within the human and mouse sequences showed less than 1% sequence conservation although we identified multiple conserved motifs. Of the 204 human lncRNAs, 21 overlapped with syntenic mouse lncRNAs, of which 5 were differentially expressed in both species. Amongst these syntenic lncRNAs was IL7-AS (antisense), which was induced in multiple cells types and shown to regulate the production of the pro-inflammatory mediator interleukin-6 in both human and mouse cells. In summary, we have identified and characterised those lncRNAs that are differentially expressed following activation of the human and mouse innate immune response and believe that these catalogues will provide the foundation for the future analysis of the role of lncRNAs in immune and inflammatory responses.